Carbon nanostructures for high-frequency line-filtering supercapacitors - M. Santhosh, Neelakandan; Cvelbar, Uros (Frontiers in Nanotechnology, 2024)
Supercapacitors (SCs) are considered one of the front-runner energy storage devices for future electronic and automobile device applications. Even though their high-power densities, fast charge/discharge, and long cycling stabilities make them promising for future applications, their charge-discharge takes place below 1 Hz, a major issue for using them as capacitors for line filtering applications. Therefore, developing ultrafast electrochemical supercapacitors with alternating current (AC) line filtering functions has gained research attention to replace conventional aluminum electrolytic capacitors (AEC). Most available SCs possess resistive features rather than capacitive at 120 Hz because of the electrode geometry and configurations, which is a bottleneck in the research of line-filtering SCs. Addressing this challenge could be possible by developing novel electrode materials using hybrid nanostructures to meet the critical requirements for line filtering functions. This minireview focuses on the advancement and challenges of carbon nanostructure-based electrode materials for AC line filtering applications and the future directions of this growing research area.